SAT0516 Influence of ethnicity on clinical pain in patients with osteoarthritis versus rheumatoid arthritis: contribution of level of education and depression. (15th June 2017) - Castrejon, I; Chua, J; Block, JA; Bradley, LA; Yazici, Y; Shakoor, N
Abstract : Background: The experience of pain is characterized by inter-individual and group variability, with ethnicity being one potential contributing factor. In a systematic review, it was shown how African Americans (AA) demonstrated lower pain tolerance in experimental studies 1 . Pain is the most common and troubling symptom in patients with osteoarthritis (OA) -maybe reflecting damage- and in patients with rheumatoid arthritis (RA) -maybe reflecting synovitis- but other pain mechanisms are important. Objectives: To investigate the influence of ethnicity on clinical pain and other outcomes and to identify potential predictors of higher scores for pain in AA and Hispanic patients with OA or RA seen in routine care. Methods: As part of their clinic visit, all patients complete a multidimensional health assessment questionnaire (MDHAQ) at 2 academic sites. MDHAQ includes 0–10 visual analogue scales (VAS) for pain, physical function, and a patient global evaluation (PATGL), and a depression score between others. The MDHAQ also include demographic data and patients "self-identify" their ethnicity. One random visit with complete questionnaire data for each OA (ICD-9=715.0) and RA (ICD-9=714.0) patient from each site was included in this analysis. Comparison according to patients' self-reported ethnicity -White, African-American (AA) or Hispanics- were performed using ANOVA and chi-squared. Multiple regression models were performed to identify independent explanatory variables for clinical pain in AA and Hispanics groups versus White. Results: The study included 402 OA patients and RA 373. There were no differences in age and gender between ethnicity groups in both diagnostic groups. Years of education were highest in the White followed by AA and then Hispanics in both OA and RA. AA and Hispanics showed statistically significantly higher scores for pain (6.6 vs 5.3 in OA, p<0.001; 5.7 vs 4.4 in RA, p<0.001) and lower physical function (3.2 vs 1.9 in OA, P<0.001; 3.2 vs 1.9 in RA, p<0.001) in comparison with Whites in both diagnostic groups. A lower level of education and a higher level of depression predicted greater pain on a MDHAQ in OA in separate models for AA and Hispanic patients and in RA in Hispanic patients (Table). Conclusions: AA and Hispanic patients had higher level of pain than Whites, but these differences are mainly influenced by level of education and level of depression in OA and RA patients. These results support the biopsychosociocultural model of pain in which, ethnic group differences may be determined by multiple mechanisms including socio-cultural as education, and psychological as depression, in addition to biological pathways. References: Rahim-Williams B, Riley JL, et al. Pain Med 2012, 13(4):522–540. Disclosure of Interest: None declared